Behavior in Children with Fetal Alcohol Spectrum Disorders in Remote Australia: A Population-Based Study. Issue 7 (September 2017) - Tsang, Tracey W.; Carmichael Olson, Heather; Latimer, Jane; Fitzpatrick, James; Hand, Marmingee; Oscar, June; Carter, Maureen; Elliott, Elizabeth J.
ABSTRACT: Objective: To document behavior in children residing in very remote Western Australian communities as rated by parent/caregivers and teachers. We hypothesized that children with fetal alcohol spectrum disorders (FASD) would have higher rates of problematic behavior than children without FASD. Methods: The Child Behavior Checklist (CBCL; n = 97), and Teacher Report Form (TRF; n = 106) were used in this population-based study. Raw scores, proportions scoring within "Normal/Borderline/Clinical" ranges, and frequencies of Critical items were determined. Mann–Whitney U and χ 2 tests were used for between-group comparisons. Results: Children were aged from 7.5 to 9.6 years, and 19% had FASD. Academic performance was commonly rated in the "Borderline/Clinical" range (73%). Teacher-rated scores were poorer in the FASD group on 15 scales encompassing total and internalizing problems, adaptive function, academic performance, attention, withdrawn/depressed, social problems, posttraumatic stress, thought problems, and sluggish cognitive tempo ( p < .05). More children in the FASD group had scores in the "Borderline/Clinical" range on 11 TRF scales ( p < .05). "Physically attacks people" was the most prevalent Critical item endorsed by teachers for the total cohort (22%). "Talks about killing self" was endorsed by teachers more often in the FASD group (14%) than the Non-FASD group (1%; p = .03). There were no significant differences between groups in parent-reported CBCL scores after adjustment for multiple comparison testing. Conclusion: This study demonstrates that children with FASD have more teacher-reported behavioral impairment than children without FASD. In remote Australian communities, academic performance is poor.